Uniform asymptotic stability of a fractional tuberculosis model - Wojtak, Weronika (2018)
We propose a Caputo type fractional-order mathematical model for the transmission dynamics of tuberculosis (TB). Uniform asymptotic stability of the unique endemic equilibrium of the fractional-order TB model is proved, for any α (0, 1). Numerical simulations for the stability of the endemic equilibrium are provided.